Relações entre traços funcionais ecologicamente importantes de espécies arbustivo-arbóreas de cerrado - Abe, Natália (Universidade Federal de São Carlos, 2016)
The so-called "Plant Ecology Strategy Scheme" groups species into categories along the spectrum of their functional traits. When two or more important functional traits are correlated between concurrent species, they define a strategic dimension. There are four main dimensions of ecological strategies for establishing the relationships among functional traits of plants: maximum plant height, size of branches and leaves, leaf structure and physiology, and seed production. Traits that may define these dimensions include: maximum plant height, wood density, leaf area, specific leaf area, fruit size, and seed size. We analysed the relationships among the traits in cerrado woody species and compared the results with those found in tropical forests. In this dissertation, we presented our results in a single chapter, written in english. We measured these traits from 28 woody species at the Vaçununga State Park, southeastern Brazil. We found two significant relationships: between fruit size and seed size and between fruit size and leaf area. We also identified two ecological strategies: species with high specific leaf area and species with low specific leaf area. Cerrado and forest woody species seem to have distinct ecological strategies, probably due to the different environmental pressures to which they are submitted.
Keywords: Estratégias ecológicas; Traços funcionais; Savana; Modelo de equações estruturais; Ecological strategy; Functional trait; Structural equation model; CIENCIAS BIOLOGICAS::ECOLOGIA